The use of silica sand, zeolite and active charcoal to reduce BOD, COD, and TSS of laundry waste water as a biology learning resources - Moch Assiddieq; Satya Darmayani; Wirapati Kudonowarso (University of Muhammadiyah Malang, 2017)
The aquatic environment contaminated with detergent waste in high concentrations can endanger the lives human and biota in the water. This study aimed to determine the decrease of BOD, COD and TSS content of laundry liquid waste by using filter media of silica sand, zeolite, and activated charcoal. Filter medium 1a can reduce BOD level from 98.6 mg/L to 58.80 mg/L (40.36%), while medium 1b can decrease BOD level to 21.20 mg/L (78.48%). It showed that media 1a had not fulfilled the quality standard of BOD of waste water that is 50 mg/L, while media 1b had fulfilled the standard of quality. Filter media 1a can decrease COD level from 210 mg/L to 78.80 mg/L (62.47%), whereas medium 1b can decrease COD to 25.60 mg/L (87.80%). This showed that media 1a and media 1b had met the quality standard of COD of waste water that is 100 mg/L. Filter media 1a can decrease TSS level from 465 mg/L to 122.5 mg/L (73.65%), whereas medium 1b can decrease TSS level to 52.3 mg/L (88.75%). This showed that media 1a and media 1b had met the quality standard of TSS of waste water that is 150 mg/L.